Logistic regression in R - Karaca, Alicem; Bašta, Milan; Malá, Ivana, 1962-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2019)
Logistic regression has a wide use of range thanks to its normality free nature. Instead offitting a straight line or hyperplane, the logistic regression model uses the logistic function tosqueeze the output of a linear equation between 0 and 1. This future makes logistic regressionone of the best option for working on a classification problem or predicating a binarydependent variable. Statistical compute programs like R studio makes these statisticalapplications more usable. In this study, logistic regression model created on R studio forexplaining intention of job leave. Moreover, created models are tested and their efficiency isillustrated.Today's economic status, globalization, rapidly increasing competition and technologicalinnovations have caused many businesses to be shut down and many employees areunemployed. The uncertainty created by all these developments has also been reflected inemployee and employer relations and has made the issue of job security an even moreimportant issue. The main aim of the research carried out within the scope of the thesis studyis to measure the job security satisfaction of the employees in tourism sectors and to revealthe relationship of this satisfaction with organizational commitment, job stress and intentionto job leave, and to test the hypotheses of the study in the light of these data.
Vedoucí práce: Milan Bašta
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: quantitative economic analysis [obor dipl. práce]; diplomové práce; master's theses